2001
DOI: 10.1046/j.1439-0507.2001.00686.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological data of cryptococcosis in Austria, Germany and Switzerland: part of the ECMM survey in Europe

Abstract: The data raised for Cryptococcus neoformans and cryptococcosis in Austria, Germany and Switzerland during the period from July 1997 to December 1999 are presented and analysed according to the epidemiological criteria. This is part of the ECMM survey in Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
1
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 8 publications
4
22
1
2
Order By: Relevance
“…These findings are promising in the search for new options against infections caused by Candida spp. and Cryptococcus spp., particularly with the continuous increase of opportunistic fungal resistance to available treatments, the emergence of rare species of Candida [55], and the increasing number of infections by Cryptococcus neoformans and C. gattii [56]. …”
Section: Resultsmentioning
confidence: 99%
“…These findings are promising in the search for new options against infections caused by Candida spp. and Cryptococcus spp., particularly with the continuous increase of opportunistic fungal resistance to available treatments, the emergence of rare species of Candida [55], and the increasing number of infections by Cryptococcus neoformans and C. gattii [56]. …”
Section: Resultsmentioning
confidence: 99%
“…This new classification is based on the observation that considerable phylogenetic divergence can be inferred in DNA sequence comparisons and in RFLP clustering [1,2,54]. The proposal, however, ignores the intermediate serotype AD [21,22]. As Lengeler et al [3] and Chaturvedi [55] have reported, the diploid or aneuploid AD strains are a result of mating between serotype A and serotype D, that is, between C. n. var.…”
Section: N Var Neoformansmentioning
confidence: 99%
“…gattii isolates were identified as two representatives of VGIII and one of VGIV. Additional epidemiological data have been collected as a part of the ECMM survey [21].…”
Section: N Var Neoformansmentioning
confidence: 99%
“…neoformans is described scarcely, except in some European countries and the United States. 2,[5][6][7][8] Due to the significant differences in the biochemistry and genetics of the variety gattii, 9 the yeast is now reclassified as a separate species, Cryptococcus gattii. 10 Cryptococcus gattii is restricted to tropical and subtropical regions and tends to infect immunocompetent hosts.…”
Section: Introductionmentioning
confidence: 99%